2009
DOI: 10.3991/ijet.v4i4.974
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Need of Mobile ICT Learning as an Elderly Learning Tool

Abstract: With a rapid deployment of mobile devices, mobile learning gives rise to new possibilities for extending learning opportunities. Nevertheless, current research on mobile learning has mostly been aimed at enhancing learning of school or college students. In this light, the paper seeks to throw light on the potential of mobile learning for elderly. We describe in this paper a research study for examining needs that determine the adoption and usage of mobile devices by elderly population. The elderly are an often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…These differences are particularly pronounced between the highly educated and those with a lower level of education since the highly educated have more opportunities to work longer (Zaid & Unt, 2019). In relation to the older population of potentially retired workers who may be additionally included in the labour market, Lam and Chung (2009) emphasize the need for their retraining or training for new work skills. Employment of the elderly is one of the indicators of active aging, and the continued work of the elderly who have acquired the conditions for retirement is positively correlated with the state's gross income (Zaid & Unt, 2019).…”
Section: Aging and Lifelong Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences are particularly pronounced between the highly educated and those with a lower level of education since the highly educated have more opportunities to work longer (Zaid & Unt, 2019). In relation to the older population of potentially retired workers who may be additionally included in the labour market, Lam and Chung (2009) emphasize the need for their retraining or training for new work skills. Employment of the elderly is one of the indicators of active aging, and the continued work of the elderly who have acquired the conditions for retirement is positively correlated with the state's gross income (Zaid & Unt, 2019).…”
Section: Aging and Lifelong Learningmentioning
confidence: 99%
“…They believe that social networks are used by young people who want publicity and superficial friendships. Older people's resistance to the use of ICT also stems from their unfavourable attitude towards learning something new (Lam & Chung, 2009). Schreurs et al (2017) point to positive shifts in the communication of old people with family and friends using ICT and the Internet (mail, Skype) and the exchange of photographs, but note that the low digital literacy of old is a barrier to new learning linked with self-confidence.…”
Section: The Obstacles Of Lifelong Learning and The Use Of Ictmentioning
confidence: 99%
“…As Lam & Chung (2009) point out in the results of their research, the interface of the mobile device and the applications or tools used is very important when we teach elderly people. The interface must be as simple as possible; there should be no multiple menus or overlaying windows.…”
Section: Teaching Digital Immigrants With Mallmentioning
confidence: 99%
“…Some studies have suggested that a lack of sufficient knowledge and experience regarding the use of digital devices may explain the digital divide [ 2 , 41 ]. Besides the limitations in digital literacy and lack of friendly hardware designs (e.g., small screen sizes) faced by older adults [ 42 ], few studies have addressed the issues of ICT access and the digital divide among older adults in Hong Kong. Thus, a better understanding of this phenomenon is needed to inform the development of interventions to address the needs of these older adults.…”
Section: Introductionmentioning
confidence: 99%